Potensi Kebijaksanaan Kontrak Pemeliharaan Mesin dalam Menunjang Keberhasilan Mekanisme Industri Pertanian - Hennie Husniah; Udjiana S. Pasaribu; A.H. Halim; B.P. Iskandar (Institute of Research and Community Outreach - Petra Christian University, 2016)
In this paper we discuss a mathematical model of maintenance policy for certain type of agricultural equipments. It is assumed that the equipments are repairable and sold with two-dimensional warranty, i.e. a warranty with two scales of limit, such as the age of the equipment and the usage of the equipment. As an example in the case of automobile, the warranty is cease whenever the age of the automobile reaches 5 years or its mileage reaches 50.000 km, whichever occurs first. The model is intended to provide the best contract-based preventive maintenance (PM) strategy chosen from available options. A method to determine the optimal cost of service contract, both from user and producer view points, is presented. Numerical simulations reveal that the resulting optimal strategy depends on the level of the consumer usage pattern. In this paper we show that the selection of optimal policy is potential in supporting the performance of mechanization in agricultural industry in terms of choosing the best strategy to maintain agricultural equipments effectively (is able to reduce the failure rate of the equipment) with a minimal cost.